The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1103/physreve.83.051910
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic microfluidic ratchet based on the deformation of individual cells

Abstract: We present a microfluidic ratchet that exploits the deformation of individual cells through microscale funnel constrictions. The threshold pressure required to transport single cells through such constrictions is greater against the direction of taper than along the direction of taper. This physical asymmetry combined with an oscillatory excitation can enable selective and irreversible transport of individual cells in low Reynolds number flow. We devised a microfluidic device to measure the pressure asymmetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 26 publications
2
69
0
Order By: Relevance
“…Additional advantages of microfluidics analysis include the requirement for small sample volumes, low-cost, and high resolution and sensitivity [35]. To experimentally test a prototype microfluidic RBC deformability device, normal and oxidatively damaged RBC were measured in a small sample of blood donors over several weeks [43,44]. As demonstrated in this study, microfluidics provided reproducible intra-and inter-individual data and demonstrated its utility in detecting oxidatively damaged RBC.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Additional advantages of microfluidics analysis include the requirement for small sample volumes, low-cost, and high resolution and sensitivity [35]. To experimentally test a prototype microfluidic RBC deformability device, normal and oxidatively damaged RBC were measured in a small sample of blood donors over several weeks [43,44]. As demonstrated in this study, microfluidics provided reproducible intra-and inter-individual data and demonstrated its utility in detecting oxidatively damaged RBC.…”
Section: Introductionmentioning
confidence: 80%
“…(1) in order to correct for the variation of red cell sizes as well as funnel pore geometries [43,44]. Although the Law of Laplace model has been traditionally applied to micropipette aspiration where a part of the cell membrane is suctioned into a circular orifice, this model makes no assumptions about the geometry of the orifice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations